Hadith Learning and Salafi Educational Epistemology in Wahdah Islamiyah Makassar - Radhie Munadi; Nur Hasti; Abd. Bashir Fatmal; Arifuddin Ahmad (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
This study examines the understanding of Hadith within Wahdah Islamiyah and its implications for education and da’wah. Using a qualitative field research approach, data were collected through interviews, observations, and documentation involving organizational leaders, preachers, and educational figures. The study analyzes Wahdah Islamiyah’s methodological orientation, epistemological foundations, and influence on religious learning and preaching activities. The findings show that Wahdah Islamiyah adopts a predominantly textual approach rooted in the manhaj al-salaf, emphasizing adherence to the Qur’an, Sunnah, and interpretations of classical scholars. Hadith is understood through a framework prioritizing textual authenticity, scholarly authority, and methodological discipline. This orientation significantly shapes the organization’s educational and da’wah systems by encouraging structured learning, moral development, and doctrinal consistency. The study also reveals that Wahdah Islamiyah seeks to preserve the continuity of Islamic intellectual tradition, strengthen religious literacy, maintain theological stability, and reinforce orthodox Sunni identity within contemporary Muslim society. Furthermore, this approach functions as an instrument for safeguarding religious understanding from subjective interpretation while reinforcing organizational identity and sustaining the transmission of Islamic teachings across educational institutions contemporarily. “This study contributes to the discourse on Hadith pedagogy by demonstrating how Salafi-oriented organizations institutionalize textual Hadith learning within integrated formal and nonformal educational systems.”